Glucagon-like peptide-1 receptor overexpression in cancer and its impact on clinical applications - Körner, Meike; Christ, Emanuel; Wild, Damian; Reubi, Jean Claude (Frontiers in Endocrinology, 2012)
Peptide hormones of the glucagon-like peptide (GLP) family play an increasing clinical role, such as GLP-1 in diabetes therapy. Moreover, GLP receptors are over-expressed in various human tumor types and therefore represent molecular targets for important clinical applications. In particular, virtually all benign insulinomas highly over-express GLP-1 receptors (GLP-1R). Targeting GLP-1R with the stable GLP-1 analogs 111In-DOTA/ DPTA-exendin-4 offers a new approach to successfully localize these small tumors. This non-invasive technique has the potential to replace the invasive localization of insulinomas by selective arterial stimulation and venous sampling. Malignant insulinomas, in contrast to their benign counterparts, express GLP-1R in only one third of the cases, while they more often express the somatostatin type 2 receptors. Importantly, one of the two receptors appears to be always expressed in malignant insulinomas. The GLP-1R overexpression in selected cancers is worth to be kept in mind with regard to the increasing use of GLP-1 analogs for diabetes therapy. While the functional role of GLP-1R in neoplasia is not known yet, it may be safe to monitore patients undergoing GLP-1 therapy carefully.